2016
DOI: 10.1177/0739986316660775
|View full text |Cite
|
Sign up to set email alerts
|

Grit Under Duress

Abstract: Undocumented Latina/o college students face obstacles and stressors; their stressful experiences and academic strengths merit empirical attention. This cross-sectional, mixed-methods study explored stress, depression, grit, and grade point average (GPA) of 84 non-citizen, Latina/o first-generation college students with a comparison group of 180 citizen, Latina/o first-generation college students in Maryland. Qualitative interviews were conducted with 21 non-citizens and 26 citizens, after conducting a quantita… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
24
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 74 publications
(28 citation statements)
references
References 21 publications
2
24
0
2
Order By: Relevance
“…C. Lee, 2017;Lee & Sohn, 2017;Li et al, 2018;Lin & Chang, 2017;Mason, 2018;Muenks et al, 2017;Sheehan, 2014;Strayhorn, 2014;Tovar-García, 2017;Wang et al, 2017;Williams, 2017), whereas one study reported a significant negative result (Climer, 2017). Six studies reported mixed results (Al-Mutawah & Fateel, 2018;Cross, 2014;Kelly et al, 2014;O'Neal et al, 2016;Pate et al, 2017;Rojas, 2015) and eight studies reported nonsignificant results (Batres, 2011;Bazelais, Lemay, & Doleck, 2016;Engel, 2013;Flanagan & Einarson, 2017;Palisoc et al, 2017;Saunders-Scott et al, 2018;Smith, 2017;Zurlo, 2017).…”
Section: Overall Gritmentioning
confidence: 99%
“…C. Lee, 2017;Lee & Sohn, 2017;Li et al, 2018;Lin & Chang, 2017;Mason, 2018;Muenks et al, 2017;Sheehan, 2014;Strayhorn, 2014;Tovar-García, 2017;Wang et al, 2017;Williams, 2017), whereas one study reported a significant negative result (Climer, 2017). Six studies reported mixed results (Al-Mutawah & Fateel, 2018;Cross, 2014;Kelly et al, 2014;O'Neal et al, 2016;Pate et al, 2017;Rojas, 2015) and eight studies reported nonsignificant results (Batres, 2011;Bazelais, Lemay, & Doleck, 2016;Engel, 2013;Flanagan & Einarson, 2017;Palisoc et al, 2017;Saunders-Scott et al, 2018;Smith, 2017;Zurlo, 2017).…”
Section: Overall Gritmentioning
confidence: 99%
“…The empirical support for the rationale of selecting grit and engagement as the mediators between stress and achievement is that stress is related to the socioemotional factors of motivation and engagement (e.g., Choudhuri, Santiago-Rivera, & Garrett, 2012), so grit and engagement may play a role in the process of how stress impacts achievement. Also, grit is conceptualized as a socioemotional factor which may be used to overcome stressful obstacles (O'Neal et al, 2016), and grit is related to the motivation construct of perseverance among ethnic minority youth (Eskreis-Winkler, Shulman, Beal, & Duckworth, 2014). Grit has two subscales -consistency of interests and perseverance of effort -which indicate a constant focus on a single goal (consistency of interests) and unwavering commitment to that goal (perseverance of effort) despite obstacles (Duckworth et al, 2007).…”
Section: Stress and Achievementmentioning
confidence: 99%
“…Optimism can play a significant role in the retention of college students by fostering determination (e.g., Solberg Nes, Evans, & Segerstrom, 2009), also referred to as perseverance or grit. Many Latino students perceive that hard work, dedication, and effort contribute to their academic success (Cavazos, Johnson, Fielding et al, 2010;O'Neal, Espino, Goldthrite et al, 2016). As found by Chemers et al (2001), optimistic students perceive their university experiences not as threats but as challenges, which they believe they can successfully handle.…”
Section: Competency Beliefs Determination and Optimismmentioning
confidence: 96%